Architecture as a beauty of art and culture in Indonesia - Ayub Muktiono (Sean Institute, 2024)
Architecture is not only understood as the physical form of buildings, but also as a manifestation of community creativity in responding to cultural and historical values. Architecture is not only understood as the physical form of buildings, but also as a manifestation of community creativity in responding to cultural and historical values. This research uses a qualitative approach with descriptive methods. The research results show that architecture in Indonesia is not only a physical structure, but also a three-dimensional expression of human behavior which is reflected in its physical form. Architecture plays a central role in reflecting and shaping human daily life, becoming a visual narrative that represents identity and cultural values. The selection of traditional elements, the use of local materials, and the concept of sustainability are the keys to creating architecture that is not only aesthetic but also celebrates the richness of Indonesian art and culture. With the intelligent integration of these elements, architecture becomes an authentic form of artistic and cultural identity, creating spaces that combine practical function with the beauty and diversity of Indonesia's cultural heritage.